Chemical Recycling of Epoxy Thermosets: From Sources to Wastes - Shuhan Zhang; Enjian He; Huan Liang; Zhijun Yang; Yixuan Wang; Zhongqiang Yang; Chao Gao; Guoli Wang; Yen Wei; Yan Ji (Actuators)
As one of the most widely used thermosets due to its excellent performances, epoxy resin (EP) is widely used in various fields and often employed as a component of composite actuator devices, strengthening their mechanical properties. However, the expanding production of EP inevitably leads to the accumulation of waste end-of-life equipment and the corresponding increasingly serious environmental problems. This review summarizes the recycling strategies of EP, divided into two perspectives: recycling from wastes and sources. Chemical recycling is expected to be the future of waste EP treatment, and we discuss the chemical recycling methods of existing waste EP based on different mechanisms, including the selective cleavage of ester bonds, C–N bonds, and C–O bonds. On the other hand, epoxy vitrimer networks based on various dynamic covalent linkages are also outlined, which can respond to multiple external stimuli and provide materials with recyclability from the origin. Therefore, the use of epoxy vitrimer actuators can prevent waste generation throughout the whole lifecycle. We present some issues of concern in both waste-based and source-based recycling strategies and emphasize the significance of scaling-up. Finally, we summarized the current situation and present some future perspectives with the aim of making practical contributions to environmental issues.